Treatment of medical, psychiatric, and substance-use comorbidities in people infected with HIV who use drugs - Altice, F.L.; Kamarulzaman, A.; Soriano, V.V.; Schechter, M.; Friedland, G.H. (2010)
HIV-infected drug users have increased age-matched morbidity and mortality compared with HIV-infected people who do not use drugs. Substance-use disorders negatively affect the health of HIV-infected drug users, who also have frequent medical and psychiatric comorbidities that complicate HIV treatment and prevention. Evidence-based treatments are available for the management of substance-use disorders, mental illness, HIV and other infectious complications such as viral hepatitis and tuberculosis, and many non-HIV-associated comorbidities. Tuberculosis co-infection in HIV-infected drug users, including disease caused by drug-resistant strains, is acquired and transmitted as a consequence of inadequate prescription of antiretroviral therapy, poor adherence, and repeated interfaces with congregate settings such as prisons. Medication-assisted therapies provide the strongest evidence for HIV treatment and prevention efforts, yet are often not available where they are needed most. Antiretroviral therapy, when prescribed and adherence is at an optimum, improves health-related outcomes for HIV infection and many of its comorbidities, including tuberculosis, viral hepatitis, and renal and cardiovascular disease. Simultaneous clinical management of multiple comorbidities in HIV-infected drug users might result in complex pharmacokinetic drug interactions that must be adequately addressed Moreover, interventions to improve adherence to treatment, including integration of health services delivery, are needed. Multifaceted, interdisciplinary approaches are urgently needed to achieve parity in health outcomes in HIV-infected drug users